Home based exercise to improve turning and mobility performance among community dwelling older adults: protocol for a randomized controlled trial - Ashari, Asmidawati; Hamid, T.; Hussain, R.; Hill, Keith (BioMed Central Ltd, 2014)
Background: Turning is a common activity for older people, and is one of the activities commonly associated with falls during walking. Falls that occur while walking and turning have also been associated with an increased risk of hip fracture in older people. Despite the importance of stability during turning, there has been little focus on identifying this impairment in at risk older people, or in evaluating interventions aiming to improve this outcome. This study will evaluate the effectiveness of a 16 week tailored home based exercise program in older adults aged (50 years and above) who were identified as having unsteadiness during turning.Methods/Design: A single blind randomized controlled trial will be conducted, with assessors blind to group allocation. Study participants will be aged 50 years and above, living in the community and have been identified as having impaired turning ability [outside of age and gender normal limits on the Step Quick Turn (180 degree turn) task on the Neurocom® Balance Master with long plate]. After a comprehensive baseline assessment, those classified as having balance impairment while turning will be randomized to intervention or control group. The intervention group will receive a 16 week individualized balance and strength home exercise program, based on the Otago Exercise Program with additional exercises focused on improving turning ability. Intervention group will attend four visit to the assessment centre over 16 weeks period, for provision, monitoring, modification of the exercise and encourage ongoing participation. Participants in the control group will continue with their usual activities. All participants will be re-assessed on completion of the 16 week program. Primary outcome measures will be the Step Quick Turn Test and Timed-Up and Go test. Secondary outcomes will include other clinical measures of balance, psychological aspects of falls, incidence of falls and falls risk factors. Discussion: Results of this study will provide useful information for clinicians on the types of exercises to improve turning ability in older people with increased falls risk and the effectiveness of these exercises in improving outcomes.